CULTURAL CONTENT ANALYSIS OF AN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOO GRADE THREE IN CIANJUR, WEST JAVA - Ihsan Nur Iman Faris (Journal of English and Education, 2014)
This article reports the result of the research investigating cultural content of an English textbook for senior high school grade three in Cianjur, West Java. The data of the research were collected from reading passages in the English textbook for senior high school entitled “Look Ahead”, book three published by Airlangga publisher. To reveal what cultures are represented in the textbook, the cultural contents are categorized into the source culture, the target culture, or the international culture (Cortazzi Jin, 1999). To reveal how the cultures are represented in the textbook, the cultural contents are categorized into the aesthetic sense, the sociological sense, the semantic sense, or the pragmatic sense (Adaskou, Britten Fahsi, 1990). The research finds that the target culture is predominant in the textbook. The investigation found that 77.05% cultural contents refer to the target culture, 13.11% cultural contents refer to the source culture, and 09.84% cultural contents refer to the international culture.  Regarding how cultures are represented in the textbook, generally culture is represented by the aesthetic sense (37.70%), the sociological sense (31.15%), the pragmatic sense (19.67%) and the semantic sense (11.48%). Based on the findings it is recommended that more source culture and international culture be included in the textbook.